TPA Privacy Protection with Blowfish Encryption - Dr. Roopam Gupta, Pritam Khatarkar,Prof. Vikas Rohit,Dr. Anjana Pandey, (Design Engineering, 2021)
In today’s technological environment, cloud computing is the latest buzzword. Despite the excitement, many people are unsure what cloud computing is, especially since the term can be used to refer to nearly anything. The next-generation architecture of the IT enterprise has been envisioned as cloud computing. It moves application software and databases to centralised large datacenters, where data and service management may be shaky. This novel paradigm introduces a slew of new security issues that have yet to be fully grasped. This study investigates the problem of ensuring data storage integrity in Cloud Computing. On behalf of the cloud client, we evaluate the job of allowing a third-party auditor (TPA) to verify the integrity of dynamic data stored in the cloud. In order to securely deploy an effective third-party auditor, the following two major needs must be fulfilled (TPA): 1) The TPA should be able to audit cloud data storage efficiently without requiring a local copy of the data or imposing any additional online burden on the cloud user; 2) the third-party auditing process should not introduce any new vulnerabilities affecting user data privacy.